Speaking Games: Meningkatkan Kemampuan Berbicara Bahasa Inggris Siswa SMA Melalui Zoom Dengan Permainan Interaktif - Lina Farsia; Ika Kana Trisnawati; Annisa Sucianda (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2025)
Learning English as a foreign language is one of the most important yet difficult skills for high school students to develop. Karena mereka tidak memiliki banyak kesempatan untuk berbicara secara aktif di kelas, banyak siswa di Aceh mengalami motivasi dan keyakinan yang rendah. Dengan menggunakan interactive game-based learning via Zoom, program community service ini bertujuan untuk meningkatkan kemampuan bahasa Inggris siswa. Berbagai jenis speaking games, seperti storytelling, debates, discussions, dan role-playing, digunakan untuk mendorong partisipasi, kreativitas, dan peningkatan confidence siswa. Student high school from several schools in Aceh Province participated in the program, which was conducted online for a period of four months. Students received significant opportunities to use English in a calm and enjoyable setting, which reduced anxiety and encouraged spontaneous communication. Game-based speaking activities increased students' engagement, acquisition of vocabulary, and fluency in expressing ideas. The results of this community service initiative show that integrating digital technology and game-based learning can be an innovative approach to improving English-speaking skills among high school students. The results of this initiative are expected to be published in an accredited SINTA community service journal as a practical model for improving English-speaking skills among students.